Functional differentiation of society and actor-centered institutionalism: Building an analytical tool for international studies - Paulus Santibáñez, Nelson (MAD, 2024)
Considering International Studies as a complex transdisciplinary field, the aim is to build a versatile analytical tool that from a sociological theory allows observing any dynamics of the diverse interactions developed by organized actors at a global level. The aim is to obtain such a tool through the theoretical synthesis between the Social Systems Theory (SST), (specifically the theory of the Functional Differentiation of the Society) and the Actor-Centered Institutionalism (ICA) of Scharpf and Mayntz. In its development, the proposal compares and evaluates in its compatibility/incompatibility concepts and elements coming from these traditions in order to build an appropriate tool to be socialized and taught for the analysis of international policies, with the horizon of informing, reflecting, analyzing and advising the decision making of different organizations involved in the configuration of thematic areas and arenas, understood as a thematic space of disputed goods, at different levels, ranging from the local to the global. Through this synthesis exercise, it is intended to elaborate a conceptual apparatus that provides an analytical-practical instrumental, adequate for the purpose of approaching the analysis of diverse interactive dynamics and of systemic order, typical of the world society and its regions.